Supply of Publicly Financed Services: Market and Non-Market Failures - Valkov, Alexander; Penkova–Pantaleeva, Evgenia; Gorchilova–Atanasova, Denitsa (UNWE Yearbook, 2020)
The article discusses the characteristics of the publicly financed healthcare, educational and social services with a special focus on their market and non-market failures. Traditional failures like informational asymmetry, incomplete market and territorial misbalances are tested. It becomes evident that those failures manifest not only in the cases of private supply, but also in the public sector. On the contrary, non-market failures become features of the private supply.
Keywords: Publicly financed services; Market and nonmarket failures; Public and private supply